MAPPAJA’ PRACTICES IN AGRICULTURAL COMMODITY TRADING IN THE DISTRICT OF WEST SINJAI, SINJAI REGENCY - Ermiati, Ermiati; Wahab, Abdul; Haddade, Abdul Wahid (Program Pascasarjana, UIN Alauddin Makassar, 2021)
This study will elaborate on the form of mappaja' trading, which is considered as an attractive economic issue as in its transactions, people do not use a system of weighing scales in trading their harvests, but with a cost estimation system for the goods. Therefore, in the trading practice, there is often a discrepancy between the harvest and the buyer’s expectation, because it may contain an element of gharar/obscurity of the goods, which can lead to an invalid transaction and harm one of the parties. This study indicated that the practice of mappaja' for agricultural commodities has occurred for a long time. The mechanism is by estimating the number of plants based on mutual trust and responsibility. The agricultural commodities used as the mappaja' objects are cloves and vegetables (carrots, cabbage, and tomatoes). The payment method in mappaja' practice is carried out in two ways, namely full payment and twice payment. Twice payment refers to the transaction where half of the payment was handed over on the agreement as a down payment and a sign of completion, then the rest of the payment were handed after the harvest. The condition of the plant is ready to harvest or not ready for harvest in the transaction of mappaja’. The rights and obligations of both parties are that traders are obliged to make payments to farmers according to the agreement and for the farmers, they have to keep taking good care of the plants if at the time of the transaction the condition of the plants is still not ready for harvest.